2018
DOI: 10.1161/circresaha.117.312067
|View full text |Cite
|
Sign up to set email alerts
|

Musclemotion

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
125
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(125 citation statements)
references
References 35 publications
0
125
0
Order By: Relevance
“…Videos of beating single cells were acquired for 20 s with a frame rate of 33 fps using Zeiss ELYRA LSM 780 (Zeiss). Cardiac contraction was measured with the Image J Musclemotion plugin [32]. Mean contraction was calculated for each individual cell.…”
Section: Quantitative Evaluation Of the Sarcomere Network And Cardiacmentioning
confidence: 99%
“…Videos of beating single cells were acquired for 20 s with a frame rate of 33 fps using Zeiss ELYRA LSM 780 (Zeiss). Cardiac contraction was measured with the Image J Musclemotion plugin [32]. Mean contraction was calculated for each individual cell.…”
Section: Quantitative Evaluation Of the Sarcomere Network And Cardiacmentioning
confidence: 99%
“…At days 14, 21, 30, and 50 of cardiac differentiation, we acquired the images of beating hAFSC-iPSC-CMs and hESC-CMs for analysis. We used the automated non-profit software, MUSCLEMOTION, to quantitate the changes of cardiomyocytes in terms of contractility and relaxation [19]. It was found that there were no significant differences in contraction duration, velocity, and amplitude between hAFSC-iPSC-CMs and hESC-CMs ( Figure 2).…”
Section: Contractility Of Hpsc-cmsmentioning
confidence: 99%
“…At days 15, 21, 30, and 50 of cardiac differentiation, we used a camera steadily mounted on an inverted microscope with slow-motion features (120 frames/second) to record a video of the beating hAFSC-iPSC-CMs and hESC-CMs for offline analysis. All the acquired files were analyzed using an automated nonprofit software, MUSCLEMOTION [19]. We used MUSCLEMOTION to read and convert the videos to the uncompressed AVI files, and measure the contractility profiles (i.e., contraction amplitude and velocity) of the hAFSC-iPSC-CMs and hESC-CMs [19].…”
Section: Contractility Measurements Of Hafsc-ipsc-cms and Hesc-cmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The established technologies to evaluate these functional parameters (e.g., patch clamp electrophysiology, multi-electrode arrays, optical imaging, and traction force microscopy) typically rely on low-to medium-throughput assays using single cells, 3D organoid, and/or engineered heart tissues [5,26]. However, recent developments have enabled measurement of contractility across all these configurations, based on quantification of pixel displacement in high-speed movies using a publicly available software [27]. Remarkably, it is now even possible to measure action potentials, cytosolic calcium flux, and contractility simultaneously [28].…”
Section: Introductionmentioning
confidence: 99%